First grade takes a test - Cohen, Miriam; Hoban, Lillian (New York, NY : Greenwillow Books, 1980)
The first grade is distressed by an intelligence test which fails to measure true aptitude.
Keywords: Examinations -- Fiction; Schools -- Fiction